1996
DOI: 10.2135/cropsci1996.0011183x003600030030x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Turfgrass Evapotranspiration Using Atmometers and the Penman‐Monteith Model

Abstract: Information is lacking on the precision of atmometers and empirical models used to estimate turfgrass evapotranspiration (ET). Experiments were conducted to evaluate the precision of black Bellani plates, a class A evaporation pan, and the Penman‐Monteith empirical model for estimating ET of ‘Mustang’ tall rescue (Festuca arundinacea Schreb.), ‘Meyer’ zoysiagrass (Zoysia japonica Steud.), ‘Prairie’ buffalograss [Buchloe dactyloides (Nutt.) Engelm.], and ‘Midlawn’ bermudagrass [Cynodon dactylon (L.) Pers. × tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
29
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 0 publications
4
29
0
Order By: Relevance
“…The summer K c values for bermudagrass agree with the findings of Qian et al (1996) They did not compute K c s in their work, but did report that the slope of the regression line relating ETa of Midiron to Penman Monteith ETo was equal to 0.80. Our bermudagrass K c s also agree quite well with those of Devitt et al (1992) who found K c s ranged from 0.82 to 0.89.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The summer K c values for bermudagrass agree with the findings of Qian et al (1996) They did not compute K c s in their work, but did report that the slope of the regression line relating ETa of Midiron to Penman Monteith ETo was equal to 0.80. Our bermudagrass K c s also agree quite well with those of Devitt et al (1992) who found K c s ranged from 0.82 to 0.89.…”
Section: Resultssupporting
confidence: 72%
“…Higher CVs suggest the Penman Monteith Equation is less accurate at estimating ETo during periods of unsettled weather. Qian et al (1996) reported a similar finding when relating ET of Midiron bermudagrass to ETo estimated with the Penman Monteith Equation.…”
Section: Resultssupporting
confidence: 59%
“…, Qian et al. ). A widely used version is FAO 56, developed by the United Nations Food and Agricultural Organization (Allen et al.…”
Section: Introductionmentioning
confidence: 99%
“…,b, Kim and Beard , Qian et al. , Bremer , Ebdon and DaCosta ). Such studies have shown that ET a on any date during a drying cycle depends not only on turfgrass species, but also on soil water content and thus irrigation frequency (Biran et al.…”
Section: Introductionmentioning
confidence: 99%
“…Qian et al (1996), using a black Bellani plate, found their atmometer to provide better ET estimates than a class A pan and the Penman-Monteith model, when compared to lysimeter ET. Qian et al (1996), using a black Bellani plate, found their atmometer to provide better ET estimates than a class A pan and the Penman-Monteith model, when compared to lysimeter ET.…”
mentioning
confidence: 97%